2018
DOI: 10.1037/xhp0000424
|View full text |Cite
|
Sign up to set email alerts
|

Links between temporal acuity and multisensory integration across life span.

Abstract: The temporal relationship between individual pieces of information from the different sensory modalities is one of the stronger cues to integrate such information into a unified perceptual gestalt, conveying numerous perceptual and behavioral advantages. Temporal acuity, however, varies greatly over the life span. It has previously been hypothesized that changes in temporal acuity in both development and healthy aging may thus play a key role in integrative abilities. This study tested the temporal acuity of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 102 publications
(191 reference statements)
1
36
0
Order By: Relevance
“…A second study echoed and extended these results across the lifespan [8]. This study used a SJ task with simple flashes and beeps in individuals from 6 to 80 years old.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…A second study echoed and extended these results across the lifespan [8]. This study used a SJ task with simple flashes and beeps in individuals from 6 to 80 years old.…”
Section: Introductionmentioning
confidence: 80%
“…Results showed a narrowing of the TBW throughout development and into adulthood, confirming previous studies [21, 73], with a subsequent widening of the TBW with healthy aging. In the same subjects, an increase in the canonical McGurk percept was observed throughout development and into adulthood, followed by a decrease in healthy aging [8]. A regression analysis showed that multisensory temporal processing was predictive of the rate of McGurk perception in individual participants during development and into adulthood, but was not similarly predictive during the declines observed in aging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a developmental perspective, the ability to utilize temporal cues to integrate audiovisual information emerges as early as the first year of life for both nonspeech [Lewkowicz, 1996] and speech [Lewkowicz, 2000[Lewkowicz, , 2003[Lewkowicz, , 2010 stimuli, but the size of the TBW is considerably larger than that of adults [Lewkowicz, 1996[Lewkowicz, , 2010. Across the life span, the width of the TBW follows a U-shaped pattern, with both children and older adults requiring longer temporal offset to detect audiovisual asynchrony compared with young adults [Noel, De Niear, Van der Burg, & Wallace, 2016;Stevenson, Baum, Krueger, Newhouse, & Wallace, 2018]. However, as most studies on the TBW are conducted in adults and infants, no clear conclusion has been reached about the developmental trajectory of the width of the TBW during childhood and adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…Even older adults who are free from cognitive impairment still show signs of sensory and motor decline and poor spatial sensorimotor adaptation (Bock and Schneider, 2002 ; Bock, 2005 ). More recent works also suggest that temporal sensitivity declines with age, as elderly individuals showed a great difficulty in detecting audiovisual asynchrony (Chan et al, 2014 ; Stevenson et al, 2017 ). Moreover, there seems to be indications of a slowing of the internal clock with age indicated by results from unpaced tapping tasks (Turgeon et al, 2011 ; Turgeon and Wing, 2012 ).…”
Section: Introductionmentioning
confidence: 99%